Recovery determinants of distressed banks: Regulators, market discipline, or the environment? - Thomas Kick; Michael Koetter; Tigran Poghosyan (Deutsche Bundesbank, 2010)
Based on detailed regulatory intervention data among German banks during 1994-2008, we test if supervisory measures affect the likelihood and the timing of bank recovery. Severe regulatory measures increase both the likelihood of recovery and its duration while weak measures are insignificant. Results seem not to be driven by regulators directing measures to particularly bad banks. That is, our results remain intact when we exclude banks that eventually exit the market due to restructuring mergers or moratoria. More transparent publication requirements of public incorporation that indicate more exposure to market discipline are barely or not at all significant. Increasing earnings and cleaning credit portfolios are consistently of importance to increase recovery likelihood, whereas earnings growth accelerates the timing of recovery. Macroeconomic conditions also matter for bank recovery. Hence, concerted micro- and macro-prudential policies are key to facilitate distressed bank recovery.
Keywords: G28; C41; G21; 330; Bank distress; capital support; regulation; recovery; Bankinsolvenz; Bankenpolitik; Bankenaufsicht; Deutschland